An NIR‐II Fluorescence/Dual Bioluminescence Multiplexed Imaging for In Vivo Visualizing the Location, Survival, and Differentiation of Transplanted Stem Cells. (19th November 2018) - Huang, Dehua; Lin, Suying; Wang, Qianwu; Zhang, Yejun; Li, Chunyan; Ji, Rui; Wang, Mao; Chen, Guangcun; Wang, Qiangbin
Abstract: The in vivo distribution, viability, and differentiation capability of transplanted stem cells are vital for the therapeutic efficacy of stem cell–based therapy. Herein, an NIR‐II fluorescence/dual bioluminescence multiplexed imaging method covering the visible and the second near‐infrared window from 400 to 1700 nm is successfully developed for in vivo monitoring the location, survival, and osteogenic differentiation of transplanted human mesenchymal stem cells (hMSCs) in a calvarial defect mouse model. The exogenous Ag2 S quantum dot–based fluorescence imaging in the second near‐infrared window is applied for visualizing the long‐term biodistribution of transplanted hMSCs. Endogenous red firefly luciferase (RFLuc)‐based bioluminescence imaging (BLI) and the collagen type 1 promoter–driven Gaussia luciferase (GLuc)‐based BLI are employed to report the survival and osteogenic differentiation statuses of the transplanted hMSCs. Meanwhile, by integrating the three imaging channels, multiple dynamic biological behaviors of transplanted hMSCs and the promotion effects of immunosuppression and the bone morphogenetic protein 2 on the survival and osteogenic differentiation of transplanted hMSCs are directly observed. The novel multiplexed imaging method can greatly expand the capability for multifunctional analysis of the fates and therapeutic capabilities of the transplanted stem cells, and aid in the improvement of stem cell–based regeneration therapies and their clinical translation. Abstract : An NIR‐II fluorescence/dual bioluminescence multiplexed imaging method is developed for in vivo monitoring of the location, survival, and osteogenic differentiation of transplanted human mesenchymal stem cells. The multiplexed imaging method within a broad spectral range of 400–1700 nm can greatly expand the capability for multifunctional analysis of the fates and therapeutic capabilities of the transplanted stem cells.